Plant and Fungal Food Components with Potential Activity on the Development of Microbial Oral Diseases. (17th October 2011) - Daglia, Maria; Papetti, Adele; Mascherpa, Dora; Grisoli, Pietro; Giusto, Giovanni; Lingström, Peter; Pratten, Jonathan; Signoretto, Caterina; Spratt, David A.; Wilson, Michael; Zaura, Egija; Gazzani, Gabriella
Abstract : This paper reports the content in macronutrients, free sugars, polyphenols, and inorganic ions, known to exert any positive or negative action on microbial oral disease such as caries and gingivitis, of seven food/beverages (red chicory, mushroom, raspberry, green and black tea, cranberry juice, dark beer). Tea leaves resulted the richest material in all the detected ions, anyway tea beverages resulted the richest just in fluoride. The highest content in zinc was in chicory, raspberry and mushroom. Raspberry is the richest food in strontium and boron, beer in selenium, raspberry and mushroom in copper. Beer, cranberry juice and, especially green and black tea are very rich in polyphenols, confirming these beverages as important sources of such healthy substances. The fractionation, carried out on the basis of the molecular mass (MM), of the water soluble components occurring in raspberry, chicory, and mushroom extracts (which in microbiological assays revealed the highest potential action against oral pathogens), showed that both the high and low MM fractions are active, with the low MM fractions displaying the highest potential action for all the fractionated extracts. Our findings show that more compounds that can play a different active role occur in these foods.